Current Undergraduate Dental Implantology Teaching in UK - Arminder Hare; Samantha Bird; Simon Wright; Cemal Ucer; Rabia Sannam Khan (MDPI AG, 2022)
Dental Implants are a popular treatment option for tooth replacement, with documented long-term success and survival rates of more than 95% over a period of 10 years. However, incorporating dental implantology into an undergraduate dental curriculum has issues associated. Therefore, the aim of this research was to examine and evaluate current undergraduate dental implantology education in the UK, investigate the amount of time allocated to this subject and analyse the barriers that are currently impeding the development of the programmes. An online questionnaire hosted by Online Surveys was designed, piloted, and sent to 16 dental schools providing undergraduate education in the UK. Ethical approval was gained from The University of Salford to conduct the study. Out of the 16 dental schools contacted, eight questionnaire responses were received, hence a response rate of 50% was achieved. The hours dedicated to the implant teaching programme varied from 3 h to 25 h, with a mean average of 11 h. It was identified from the results that no teaching of dental implantology was conducted in year 2; 12% of the schools responded that the subject was taught in year 1, 37% in year 3, 75% in year 4 and 50% in year 5. The methods used to deliver the programme were mainly lecture-based teaching, with only one dental school allowing students to place implants on patients. The main barriers to progression of the programme were financial (75%), followed by time limitations imposed by the curriculum (37%) and liability insurance (37%). However, there appears to be a consensus that further training beyond bachelor's degree level is required to teach implantology effectively.